2019
DOI: 10.1016/j.hal.2019.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic speciation in Protoceratium reticulatum (Dinophyceae): Evidence from morphological, molecular and ecophysiological data

Abstract: The cosmopolitan, potentially toxic dinoflagellate Protoceratium reticulatum possesses a fossilizable cyst stage which is an important paleoenvironmental indicator. Slight differences in the internal transcribed spacer ribosomal DNA (ITS rDNA) sequences of P. reticulatum have been reported, and both the motile stage and cyst morphology of P. reticulatum display phenotypic plasticity, but how these morpho-molecular variations are related with ecophysiological preferences is unknown. Here, 55 single cysts or cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 82 publications
0
12
0
Order By: Relevance
“…The case of Operculodinium centrocarpum sensu Wall and Dale 1966 is very interesting as the relationship between process length and salinity shows strong positive correlation in the Baltic Sea and the opposite in the North Pacific (Mertens et al 2009). This phenomenon can now be explained by cryptic speciation in Protoceratium reticulatum (a name of the motile stage for Operculodinium centrocarpum sensu Wall and Dale 1966) that was proposed by Mertens et al (2012a) and supported by molecular evidence recently reported by Wang et al (2019). Similarly, in low salinity seas, high variability of process development in Spiniferites cruciformis and the cyst of Gonyaulax baltica may be weakly correlated with surface salinity (Ellegaard et al 2002;Mudie et al, 2002).…”
Section: Biogeographical Patternsmentioning
confidence: 62%
“…The case of Operculodinium centrocarpum sensu Wall and Dale 1966 is very interesting as the relationship between process length and salinity shows strong positive correlation in the Baltic Sea and the opposite in the North Pacific (Mertens et al 2009). This phenomenon can now be explained by cryptic speciation in Protoceratium reticulatum (a name of the motile stage for Operculodinium centrocarpum sensu Wall and Dale 1966) that was proposed by Mertens et al (2012a) and supported by molecular evidence recently reported by Wang et al (2019). Similarly, in low salinity seas, high variability of process development in Spiniferites cruciformis and the cyst of Gonyaulax baltica may be weakly correlated with surface salinity (Ellegaard et al 2002;Mudie et al, 2002).…”
Section: Biogeographical Patternsmentioning
confidence: 62%
“…The only other relatively common species is the thermophilic Spiniferites pachydermus sensu Mertens et al (2015) (3.7-18%). Protoceratium reticulatum is a potentially yessotoxinproducing (Liu et al 2017;Wang et al 2019), bloomforming opportunistic dinoflagellate found in Japanese waters today (e.g., Koike et al 2006). It is a cosmopolitan species whose cysts, known in the literature also as Operculodinium centrocarpum sensu Wall and Dale (1966), can dominate today at high latitudes including the Okhotsk Sea (Bonnet et al 2012) and off Hachinohe, northeastern Japan, which is under the influence of the Tsugaru Warm Current (Matsuoka 1976) and Oyashio Current.…”
Section: Dinoflagellate Cyst Assemblage Biozonementioning
confidence: 99%
“…Protoceratium reticulatum (=Operculodinium centrocarpum) is considered one of the most cosmopolitan species (Wall et al, 1977;Dale, 1996;Marret et al, 2020;de Vernal et al, 2020). Recent work has shown the existence of at least three genotypes with different ecological preferences (Wang et al, 2019). Despite this, cysts of P. reticulatum have been successfully used as part of ecological signals related with environmental instability in different marine ecosystems.…”
Section: Environmental Influences On the Dinoflagellate Cyst Assemblagesmentioning
confidence: 99%